Liposomal Formulations of a Polyleucine–Antigen Conjugate as Therapeutic Vaccines against Cervical Cancer - Farrhana Z. Firdaus; Stacey Bartlett; Waleed M. Hussein; Lantian Lu; Quentin Wright; Wenbin Huang; Ummey J. Nahar; Jieru Yang; Mattaka Khongkow; Margaret Veitch; Prashamsa Koirala; Uracha R. Ruktanonchai; et al. (Pharmaceutics, 2023)
Human papilloma virus (HPV) is responsible for all cases of cervical cancer. While prophylactic vaccines are available, the development of peptide-based vaccines as a therapeutic strategy is still under investigation. In comparison with the traditional and currently used treatment strategies of chemotherapy and surgery, vaccination against HPV is a promising therapeutic option with fewer side effects. A peptide derived from the HPV-16 E7 protein, called 8Qm, in combination with adjuvants showed promise as a therapeutic vaccine. Here, the ability of polymerized natural amino acids to act as a self-adjuvating delivery system as a therapeutic vaccine was investigated for the first time. Thus, 8Qm was conjugated to polyleucine by standard solid-phase peptide synthesis and self-assembled into nanoparticles or incorporated in liposomes. The liposome bearing the 8Qm conjugate significantly increased mice survival and decreased tumor growth after a single immunization. Further, these liposomes eradicated seven-day-old well-established tumors in mice. Dendritic cell (DC)-targeting moieties were introduced to further enhance vaccine efficacy, and the newly designed liposomal vaccine was tested in mice bearing 11-day-old tumors. Interestingly, these DCs-targeting moieties did not significantly improve vaccine efficacy, whereas the simple liposomal formulation of 8Qm-polyleucine conjugate was still effective in tumor eradication. In summary, a peptide-based anticancer vaccine was developed that stimulated strong cellular immune responses without the help of a classical adjuvant.